Inner Multiplicity and Mental Health: A Soundness of Internal Voices - Trzebińska, Ewa; Gabińska, Anna (Studia Psychologica: Theoria et praxis, 2008)
The present study is concerned with the impact of inner multiplicity and multivoicedness on the quality of life. It explores the soundness of internal voices. In order to define the psychological nature of inner voices the notion of subpersonalities was used. Subpersonalities are autonomous units of the self-system; they are coherent constellations of different mental phenomena - perceptions, affects, wishes, goals, reasoning, bodily sensations and behaviors. Inner voices are meant to be phenomenal expression of those constellations. Our hypothesis was that positivity and completeness of subpersonalities were related to better mental health. The study was conducted via Internet. Participants completed the measures of subpersonalities system and personality disorders. The results show low positivity and deep emotional incompleteness of subpersonalities in personality disorders.